PENGARUH PENERAPAN STRATEGI THINKING ALOUD PAIR PROBLEM SOLVING (TAPPS) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 PAINAN - Zuhrah, Sofia; Rahmi, Rahmi; Pratiwi, Merina (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ This research was conducted based on the fact indicating that the studentsâ understanding on mathematic concept was still low, the students seemed to be less active and unable to complete the tasks given by themselves. The aim of this research was to improve the studentsâ activity and understanding on mathematic concept by using Thinking Aloud Pair Problem Solving (TAPPS) strategy in class VIII of SMPN 2 Painan. This was an experimental research whose sample was chosen by random. The instruments of the research were observation sheets and a test on the studentsâ understanding on mathematic Â concept. The result of the research revealed that after the strategy applied, the studentsâ activity improved, and their understanding on mathematic Â concept was better than that of students treating by using conventional learning strategy. This could be seen from the P-Value (0,038) which was smaller than Î±, Thus it was concluded that the use of TAPPS strategy could improve the studentsâ understanding on mathematic concept better than that of the conventional learning.Â